Volatility Spillover Among Asian Developed Stock Markets to Indonesia Stock Market During Pandemic Covid-19 - Panjaitan, Yunia; Novel, Rizky (University of Merdeka Malang, 2021)
This study aims to analyze the transmissions of volatility spillovers from China, Singapore, South Korea, and Japan stock markets to the Indonesian stock market and prove an asymmetric effect on spillover volatility. The data retrieved from the stock index of each country in the period 2020. The analytical method used is the Exponential GARCH (EGARCH) specification developed by Nelson (1991). The results of data analysis show that there was no spillover of volatility from the stock markets of China, Singapore, South Korea, and Japan to the Indonesian stock market. The data analysis results also showed an asymmetric effect on the spillover of volatility from the stock markets of China, Singapore, South Korea, and Japan to the Indonesian stock market. DOI : https://doi.org/10.26905/jkdp.v25i2.5532